Holey graphene: a unique structural derivative of graphene. Issue 4 (4th July 2017) - Lin, Yi; Liao, Yunlong; Chen, Zhongfang; Connell, John W.
ABSTRACT: Holey graphene (hG), also called graphene nanomesh, is a structural derivative of graphene. hG is formed by removing a large number of atoms from the graphitic plane to produce holes distributed on and through the atomic thickness of the graphene sheets. These holes, sometimes with abundant functional groups around their edges, impart properties that are uncommon to intact graphene but advantageous toward various applications. In this review, strategies to prepare hG and the related applications that take advantage of the unique structural motif of these materials are discussed. Prospects are then given for this emerging class of graphene derivatives. GRAPHICAL ABSTRACT: IMPACT STATEMENT Holey graphene is a novel class of graphene derivative that has in-plane porosity. It outperforms intact graphene in many applications such as nanoelectronics, sensors, energy storage, and membranes.